1992
DOI: 10.1002/j.1467-8438.1992.tb00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Injured and Silenced: Working with Workers' Compensation Claimants and Their Families

Abstract: It is not uncommon for rehabilitation and workers' compensation systems to treat the injured worker as either a passive victim or a mischievous malingerer.Much ofthe literatureregardingrehabilitation ofpeople with chronic pain and soft tissue injury speaks ofparalysis and powerlessness as if the injured person is a piece offlotsam buffeted about by the socialforces of WorkCare (and other compensation systems), the employer and the medical legal systems. This paper will review the pertinent literature and demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Related to legitimacy was the interviewees' perception that their claims were regarded as fraudulent until proved otherwise. Frankcom (1992) also observed that injured workers are assumed to be passive or frauds, and Baril et al (2003) noted that workers experience the systems as unfair, which results in frustration, anger, and anxiety. Our findings suggest that this experience goes beyond unfairness, as our interviewees considered themselves maligned, and treated without respect by bureaucrats and health professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Related to legitimacy was the interviewees' perception that their claims were regarded as fraudulent until proved otherwise. Frankcom (1992) also observed that injured workers are assumed to be passive or frauds, and Baril et al (2003) noted that workers experience the systems as unfair, which results in frustration, anger, and anxiety. Our findings suggest that this experience goes beyond unfairness, as our interviewees considered themselves maligned, and treated without respect by bureaucrats and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…602, 611). Other authors have argued that compensation systems assume that some workers are acting fraudulently, or they encourage passivity, and that this can have either antitherapeutic or therapeutic consequences (Frankcom, 1992;Lippel, 1999). Lippel suggested that the compensation process involves multiple medical examinations to prove the legitimacy of a condition, stigmatization, surveillance, suspicion, disputes regarding compensation, and consequent delays in decisions, all of which affect the health of claimants negatively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While explanations for this result are speculative, the often‐adversarial patient–physician relationship that can characterize Workers’ Compensation case management may contribute to high levels of claimant dissatisfaction with the quality of their care [26,46]. Alternatively, there may be other impediments to satisfaction, including delays in treatment [7] and a lack of input into treatment decisions [24,33,47]. As discussed below, physician decision making may also contribute to differences in outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients feel devalued as they participate in the system [19,20], noting that health care providers seem to discount their injuries, particularly self‐reported pain [8,21–23]. Other concerns center on lack of choice regarding treatments and treatment providers [20,24]. In general, Workers’ Compensation claimants seem to distrust the very health care providers who are charged with their symptom control and functional restoration [25].…”
Section: Introductionmentioning
confidence: 99%